Imaging the efficacy of UVC irradiation on superficial brain tumors and metastasis in live mice at the subcellular level1. Issue 2 (17th December 2012) - Momiyama, Masashi; Suetsugu, Atsushi; Kimura, Hiroaki; Kishimoto, Hiroyuki; Aki, Ryoichi; Yamada, Akimitsu; Sakurada, Harumi; Chishima, Takashi; Bouvet, Michael; Endo, Itaru; Hoffman, Robert M.
Abstract The effect of UVC irradiation was investigated on a model of brain cancer and a model of experimental brain metastasis. For the brain cancer model, brain cancer cells were injected stereotactically into the brain. For the brain metastasis model, lung cancer cells were injected intra‐carotidally or stereotactically. The U87 human glioma cell line was used for the brain cancer model, and the Lewis lung carcinoma (LLC) was used for the experimental brain metastasis model. Both cancer cell types were labeled with GFP in the nucleus and RFP in the cytoplasm. A craniotomy open window was used to image single cancer cells in the brain. This double labeling of the cancer cells with GFP and RFP enabled apoptosis of single cells to be imaged at the subcellular level through the craniotomy open window. UVC irradiation, beamed through the craniotomy open window, induced apoptosis in the cancer cells. UVC irradiation was effective on LLC and significantly extended survival of the mice with experimental brain metastasis. In contrast, the U87 glioma was relatively resistant to UVC irradiation. The results of this study suggest the use of UVC for treatment of superficial brain cancer or metastasis. J. Cell. Biochem. 114: 428–434, 2013. © 2012 Wiley Periodicals, Inc.